2023
DOI: 10.3390/bdcc7010055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Missing Data Types and Imputation Methods on Supervised Classifiers: An Evaluation Study

Abstract: Data completeness is one of the most common challenges that hinder the performance of data analytics platforms. Different studies have assessed the effect of missing values on different classification models based on a single evaluation metric, namely, accuracy. However, accuracy on its own is a misleading measure of classifier performance because it does not consider unbalanced datasets. This paper presents an experimental study that assesses the effect of incomplete datasets on the performance of five classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In the context of classification, a limited number of studies have compared the performance of different imputation methods [20,21]. Recently, authors in [22,23] assessed incomplete datasets' effect on classification models' performance. They found that the ratio, missing data size, and dataset balance are the most significant factors.…”
Section: From Missing Data To Imputation Methodsmentioning
confidence: 99%
“…In the context of classification, a limited number of studies have compared the performance of different imputation methods [20,21]. Recently, authors in [22,23] assessed incomplete datasets' effect on classification models' performance. They found that the ratio, missing data size, and dataset balance are the most significant factors.…”
Section: From Missing Data To Imputation Methodsmentioning
confidence: 99%